Structural prediction and copper(1) binding analyses of Csor-like hypothetical protein of Geobacillus zalihae - Musa, Nasihah (2016)
Copper is a transition metal which is essentially needed in living things. It plays various roles such as cofactor for enzymes which are important in cellular processes. However, high concentration of copper will lead to toxicity. Living organisms have metal homeostasis mechanisms in order to overcome such adversities caused by metals.In bacteria, such mechanisms help to stabilize cellular copper concentrations. To date,nine classes of copper regulation have been documented and classified based on the organisms from which they have been found. CsoR copper regulation is the most recently discovered mechanism. To date, only three CsoR proteins (from Thermus thermophilus, Mycobacterium tuberculosis and Streptomyces lividans) are structurally and functionally characterized. Hence, the effort of finding and characterizing more of these proteins from other bacterial strains are important to gain more significant comparisons of this protein across different bacterial taxa. A good platform to find and study in greater detail for such candidates would be within the pool of hypothetical proteins (HPs). HPs constitute approximately 30-40% of any given genome. They are often referred as “orphan” proteins due to their unknown functions stemming from their low sequence and/or structural homology to other known, well-characterized proteins. In this study, a scan on the complete genome of a locally isolated Geobacillus zalihae thermophile revealed the presence of a CsoR-like (CsorGz) hypothetical protein which contained CsoR-like_DUF156 domain and highly conserved Cys-His-Cys residues important for copper binding, similar to well characterized CsoR proteins.However, it only shares 30-38% sequence identity to well characterized CsoR proteins.3-D structural prediction of CsorGz-like protein via threading predicted that the protein contains three helices per monomer. Its putative, conserved copper-binding residues,Cys46-His71-Cys75, were also found to be located on α2 helix of the predicted structure similar to other CsoR proteins. Amplification of the csorGz-like open reading frame from the genome of G. zalihae was achieved and the amplicon was cloned into pET-28b expression vector for heterologous production of the protein in Escherichia coli BL21 Star Ⓡ (DE3). Native-PAGE analysis of the purified recombinant CsorGz-like protein revealed that it is a dimeric protein. Secondary structure analysis of the protein with circular dichroism revealed that it comprises of mainly α-helices, similar to well characterized CsoR proteins. Titration of Cu(I)Cl to the purified recombinant CsorGzlike protein revealed interaction of Cu(I) with the protein as revealed by UV/Vis,circular dichroism and fluorescence spectroscopy analyses, with a Kd of 6.4 x 10-5 M. It can be concluded that CsorGz-like protein, despite being a HP, contains the Cu(I) binding property thus gives more insights on copper regulator proteins in bacterial diversity.